种纸纤维素黏胶液制备方法 (2018)
本发明公开种由废纸制纤维素黏胶液方法，属于天然高分子领域，具体包括以下步骤：S1初始纸纤维素原料制备；S2对所述初始纸纤维素原料，用稀硫酸对其进行降解处理；之后，对其进行过滤、曝晒、老化和研磨处理，得到低聚合度纸纤维素原料；S3将所述低聚合度纸纤维素原料于室温溶于NaOH/NHCSNH混合水溶液中，或将其溶于低温NaOH/NHCONH混合水溶液中，得到纸纤维素黏胶液。该黏胶液可被用于生产再生纤维。本发明所提供种以废纸为原料制纤维素黏胶液方法，可被用以实现对废纸高效、高值化利用，及同比降低再生纤维生产成本。其操作条件温和，常压、室温、不涉及易挥发剧毒物等。 The invention discloses a method for preparing a cellulose viscose glue solution from waste paper, and belongs to the field of natural macromolecules. The method for preparing the cellulose viscose glue solution from the waste paper particularly comprises the following steps of S1, preparing an initial paper-cellulose raw material; S2, degrading the initial paper-cellulose raw material by using dilute sulfuric acid; afterwards, filtering, insolating, ageing and grinding the degraded initial paper-cellulose raw material, so as to obtain a paper-cellulose raw material with a low polymerization degree; S3, dissolving the paper-cellulose raw material with the low polymerization degree in an NaOH/NH2CSNH2 mixed aqueous solution at a room